MANAJEMEN PENGELOLAAN KELAS SEKOLAH DASAR PADA MASA PANDEMI - Nurpratiwiningsih, Laelia; Ervina, Dian (Jurnal Review Pendidikan Dasar : Jurnal Kajian Pendidikan dan Hasil Penelitian, 2022)
Class management is one of the most important factors in teaching and learning activities that can provide facilities in schools, especially classes to carry out various learning activities. This study aims to describe how teachers in classroom management in elementary schools during the pandemic can improve learning for the better. This study uses a qualitative approach with a descriptive method. Data collection techniques in research using observation, interviews and documentation. The results showed that classroom management carried out by teachers in grade IV at SD Negeri Dukuhwringin 01 during the pandemic was quite effective, because the learning system is carried out boldly and attractively so that it can help students at the level of understanding previous knowledge and arouse students’ enthusiasm for learning with complementary learning systems that make learning effectiveness better.